Production and Operations Management / Sixth Edition - Lockyer Keith; Muhlemann Alan; Oakland John (Pitman Publishing, 1992)
Strategy and Interfaces, The Product or Service, The Plant or Facilities, The Processes, The Programmes or Resource Plans, The People, Appendices, Index.
Strategy and Interfaces, The Product or Service, The Plant or Facilities, The Processes, The Programmes or Resource Plans, The People, Appendices, Index.